Addiction to New Technologies and Cyberbullying in the Costa Rican Context - Raquel Lozano-Blasco; Alberto Quilez-Robres; Roxana Rodriguez-Araya; Raquel Casanovas-López (MDPI AG, 2022)
Addiction to new technologies (Internet, smartphone and video games) as well as cyber-aggression presents a growing incidence at a global level. Correlational research is proposed with a sample of n = 127 Costa Rican adolescents, with a mean age of 16.32 years, comprising 67 men and 60 women. The objective was to determine the prevalence of Internet, smartphone and video game addiction and its close relationship with cyberbullying (cyber-victim role, cyberbully role and mixed role) in the Costa Rican context. The results show a high rate of abusive use (connection time) of the Internet and "smartphones", and the correlation study, multiple regressions, backward elimination method and network analysis show how the behavior of cyberbullies is moderately mediated by "Lack of control of Smartphone" and to a large extent by "Avoidance and social problem video games", while that of victims is moderately mediated by "Avoidance and social problem video games", and is slightly mediated for "Lack of control of Smartphone" and for "Lack of control of Internet". In addition, there is a strong relationship between holding both the role of cyber-victim and cyberbully, developing feelings of revenge and lack of empathy. The practical implications, and the relevance of the socio-demographic and social explanatory variables of both phenomena are discussed. It is concluded that there is evidence of an explanatory and close relationship between the phenomena of cybervictimization, cyber-aggression and addiction to the Internet, smartphone and video games.